Доменне ім’я як засіб індивідуалізації в цифровому середовищі - Петрів, Маркіян Васильович; Петрив, Маркиян Васильевич; Petriv, Markian (ВД "Гельветика", 2019)
Стаття присвячена аналізу правового режиму доменного імені як засобу індивідуалізації в цифровому середовищі. Досліджено теоретичні позиції, судову практику та правове регулювання щодо правової природи доменного імені, його поняття, співвідношення з іншими засобами індивідуалізації. На основі аналізу положень чинного законодавства визначено регулятори досліджуваних правовідносин, особливості використання доменного імені в цифровому середовищі та зміст права на доменне ім’я.

The article is devoted to the analysis of the legal regime of the domain name as a means of individualization in the digital sphere. In the scientific article there were researched the theoretical positions, judicial practice and legal regulation concerning the legal nature of the domain name, its concept, relation with other means of individualization. On the basis of the analysis of the provisions of the current legislation, the author established that domain names are the means of addressing the Internet, and the domain itself is an intangible asset, since it represents the name of an information resource that can materially be of great economic value. The author has substantiated that domain names are verbal indications, so they can be identical or similar to the degree of confusion with such objects of intellectual property rights as trademarks for goods and services, some objects of copyright, commercial names, names of legal entities, etc. Domain name is a name of a particular website that may belong to any entity (individual, legal entity). Mostly, the owners of the websites are business entities that use it for their own promotion and promotion of their products on the market. The author has proved that the Reglament of the peculiarities of registration of the second level of private domain names in the .UA domain and the Domain Rules. UA should be used as a condition of the agreement of accession, if they have a reference in the contract between the registrant and the registrar, or as a custom if there is no such reference in the contract. The author establishes that the content of the right to a domain name depends on which objects of civil rights are reflected in the verbal expression of domain names (a sign for goods and services, commercial name, indication of the origin of the goods, the object of copyright, the name of the person, etc.), and from the characteristics of such an object. The author concludes that the distinction between “domain” and “domain name” should be distinguished. The domain is the digital address of the website, and the domain name is its verb expression, information identifier, because words are easier to remember than numbers. The author established that there are two types of domains: domains created based on the encoding of country names in accordance with international standards, and second-level domains. Domain with an attachment to Ukraine is a domain .UA. It is the top-level domain of the hierarchical address space of the Internet, created on the basis of the encoding of the names of countries in accordance with international standards, to serve the address space of the Ukrainian segment of the Internet. The second level domain is part of the address space of the Internet, located at the second level of the hierarchy of names in this network.
Петрів М. В. Доменне ім’я як засіб індивідуалізації в цифровому середовищі / М. В. Петрів // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 92-96.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; доменне ім’я; Інтернет; торговельна марка; засоби індивідуалізації; інтелектуальна власність; domain name; Internet; trademark; means of individualization; intellectual property